Arab states' attitude towards the Algiers agreement 1975 (Raparin Journal of Humanities (RJH), 2024)
After the resumption of war between the Iraqi government and the Kurds in 1974, the Iraqi government sought about another plat to overcome the Kurdish revolution: it was approaching Iran, because Iranian government supported the Kurds in every way, including the military backing. The Iraqi government entered into negotiations with Iran by assistance of the Arab countries with strong ties.The Arab states did not remain silent about the events in Iraq, intensified their efforts to help both countries closer to each other and end the long-standing conflict between them, Finally, they successfully managed to sign the Algiers Agreement, Iraq and Iran were reconciliated. As the result of the agreement, the Kurds were the biggest losers because the September Revolution ended for fourteen years continued.This paper consists of an introduction, two basic topics and conclusions. The first topic discusses the role of Arab states in bringing Iraq and Iran closer together, and the second topic focuses on the Algiers agreement and the reaction of Arab states to the agreement. At the end of the study, the most important results of this study are presented in several points.